The development of the information and communication technologies sector in the Republic of Moldova - Stoian, Eugeniu; Hăbășescu, Mariana (Інформація та соціум, 2024)
The development of the ICT sector has a significant positive impact on the labor productivity of the economy, the efficiency of public administration and the citizenorientation of public services. At the microeconomic level, this translates into increased competitiveness, higher profits, better wages and a broader tax base. Making public administration more efficient reduces social costs and improves operational management, while public services become more accessible and efficient, including advanced technologies in education and health, a better managed public transport system and efficient e-services. These improvements lead to higher living standards, better educational outcomes and improved social conditions. More well-paid jobs help to reduce migration rates and improve the country’s demographic profile.